2018
DOI: 10.3390/ma11122546
|View full text |Cite
|
Sign up to set email alerts
|

Modification of a Defect-Based Fatigue Assessment Model for Al-Si-Cu Cast Alloys

Abstract: Cast parts usually inherit internal defects such as micro shrinkage pores due to the manufacturing process. In order to assess the fatigue behaviour in both finite-life and long-life fatigue regions, this paper scientifically contributes towards a defect-based fatigue design model. Extensive fatigue and fracture mechanical tests were conducted whereby the crack initiating defect size population was fractographically evaluated. Complementary in situ X-ray computed tomography scans before and during fatigue test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 64 publications
(88 reference statements)
0
14
0
Order By: Relevance
“…In terms of porosity effect on the cast component fatigue strength various studies have been conducted, thoroughly investigating crack growth behaviour [2][3][4][5] as well as statistical description taking into account the effect of pore size, location and shape [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Therein, fatigue assessment concepts like the √ area-approach of Murakami [22], or threshold-based concepts like the concept of Kitagawa and Takahashi [23], are frequently applied due to their engineering feasible applicability.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of porosity effect on the cast component fatigue strength various studies have been conducted, thoroughly investigating crack growth behaviour [2][3][4][5] as well as statistical description taking into account the effect of pore size, location and shape [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Therein, fatigue assessment concepts like the √ area-approach of Murakami [22], or threshold-based concepts like the concept of Kitagawa and Takahashi [23], are frequently applied due to their engineering feasible applicability.…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue is one of the main failure forms of engineering components of aluminum alloys [7,8]. The structural components of Al-Si series alloys work under extremely severe and complex conditions such as high stress [9,10], and the material will be in a state of plastic strain, resulting in low-cycle fatigue failure of the material [11,12]. In order to ensure the safety of components in service, it is necessary to perform a deep investigation of the fatigue characteristics of materials.…”
Section: Introductionmentioning
confidence: 99%
“…Since a preliminary study in [56] revealed that the area parameter correlates well with the stress field around the inhomogeneity, this parameter is further utilized in this work for the estimation of defect sizes. The defect size measurement methodology invoked in this work is in detail described in [57,58,59]. According to investigations in [60,61], the statistical distribution of defect sizes can be characterized by the limiting extreme value distribution of the Lognormal (LN) distribution, namely the Gumbel or Extreme Value type one distribution (EV) [62,63].…”
Section: Introductionmentioning
confidence: 99%